Cosmo‐political landscapes of Torres Strait adhi and misœri stones: Closing the gap between Islander and non‐indigenous perspectives. Issue 1 (5th January 2023) - Mitchell, Rod; Gnielinski, Friedrich von; Willsher, Josh; Elu, McRose; Wright, Duncan
ABSTRACT: Torres Strait (TS), on Australia's north‐east border, has a long history of research on pœrapœral kulal : powerful stones. Pœrapœral kulal contain vital power from site‐of‐origin and therefore their movement across the Coral‐Arafura Sea corridor provides important information about past and present human relationships (Elu 2004). With few exceptions Western models draw on anthropological, linguistic and site origin research collated by a Cambridge University field team over 100 years ago, with little detailed reassessment of stone raw material and distribution or geological and archaeological surveys conducted within the intervening period. It is also unclear how TS Islanders engage with this literature, particularly the many communities poorly represented by 19th‐century studies. In this paper, we test several assumptions influencing recent literature from contemporary islander and non‐indigenous perspectives. This includes assessing whether: (a) western scholarship models oversimplify terminology and discussion; (b) early geological assessments of substantive movement of stones is correct; and (c) movement of exotic stones was a common feature across TS. Finally, using detailed cultural, archaeology, geology, and language data sets we reinterpret the regionally‐varying role and antiquity of pœrapœral kulal within this animate cosmo‐political land and seascape. RÉSUMÉ: Le Détroit de Torres, entre l'Australie et la Papouasie, se vantent d'une longue histoire de recherche sur des pœrapœral kulal (pierres puissantes) qui contiennent de l'énergie vitale des sites sacrés, indiquant que leurs déplacements révèlent des informations importantes sur les relations humaines anciennes et contemporaines (Elu 2004). Excepté peu d'exceptions, les modèles occidentaux s'appuient sur des recherches anthropo‐linguistiques et géologiques rassemblées par une équipe de l'Université de Cambridge il y a plus de 100 ans. Peu de réévaluations détaillées se réalisèrent entretemps, soit des provenances géographiques et géologiques des pierres elles‐même, soit des prospections géologiques et archéologiques. Également, des nombreuses communautés restent malreprésentées par les études du XIXe siècle. Nous testons des hypothèses qui influencent la littérature récente, à partir des perspectives contemporaines des insulaires et des non‐autochtones, surtout les questions suivantes: a) les modèles occidentaux simplifient‐elles trop la discussion?; b) les premières évaluations géologiques des pierres furent‐elles correctes?; c) le transport des pierres était‐il universel? À partir des données culturo‐lingüistiques, archéologiques, géologiques, nous réinterprétons le rôle et l'antiquité des pœrapœral kulal au sein de ce paysage terrestre et marin animé et cosmo‐politique.